Validating proposed migration equation and parameters' values as a tool to reproduce and predict 137Cs vertical migration activity in Spanish soils. (April 2017) - Olondo, C.; Legarda, F.; Herranz, M.; Idoeta, R.
Abstract: This paper shows the procedure performed to validate the migration equation and the migration parameters' values presented in a previous paper (Legarda et al., 2011) regarding the migration of 137 Cs in Spanish mainland soils. In this paper, this model validation has been carried out checking experimentally obtained activity concentration values against those predicted by the model. This experimental data come from the measured vertical activity profiles of 8 new sampling points which are located in northern Spain. Before testing predicted values of the model, the uncertainty of those values has been assessed with the appropriate uncertainty analysis. Once establishing the uncertainty of the model, both activity concentration values, experimental versus model predicted ones, have been compared. Model validation has been performed analyzing its accuracy, studying it as a whole and also at different depth intervals. As a result, this model has been validated as a tool to predict 137 Cs behaviour in a Mediterranean environment. Graphical abstract: Highlights: A model which reproduces 137 Cs migration in soil has been validated. To validate, experimental activity profiles have been checked against predicted ones. Before checking, model's uncertainty has been assessed. Validation is performed studying the accuracy when reproducing an activity profile. A tool that predicts 137 Cs behaviour in a Mediterranean environment is given.